2003
DOI: 10.1038/sj.gene.6364026
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of GITR ligand

Abstract: The gene encoding the natural ligand of murine glucocorticoid-induced tumor necrosis factor receptor (GITR) was cloned and characterized. The putative GITR ligand (GITRL) is composed of 173 amino acids with features resembling those of type II membrane proteins and is 51% identical to the human activation-inducible TNF receptor (AITR) ligand, TL6. Expression of the GITRL is restricted to immature and mature splenic dendritic cells. GITRL binds GITR expressed on HEK 293 cells and triggers NF-kB activation. Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 14 publications
2
77
0
Order By: Relevance
“…GITR is expressed in resident macrophages, as previously demonstrated also for peritoneal and splenic macrophages (3,8,9), and is up-regulated about 3-fold following carrageenan treatment (Fig. 4D, column 3 …”
Section: Gitr and Its Ligand Are Expressed In The Lungsmentioning
confidence: 55%
“…GITR is expressed in resident macrophages, as previously demonstrated also for peritoneal and splenic macrophages (3,8,9), and is up-regulated about 3-fold following carrageenan treatment (Fig. 4D, column 3 …”
Section: Gitr and Its Ligand Are Expressed In The Lungsmentioning
confidence: 55%
“…We and others have observed that GITR triggers NF-B activation (5,24,25). Studies of the human GITR homologue, termed activation-induced TNFR-related receptor (AITR), suggest that TRAFs can play a role downstream of GITR (26,27).…”
Section: S Ignaling Pathways Triggered By Tnfr Family Members Globallmentioning
confidence: 99%
“…Recently, it has been shown that the GITR-L is expressed at high levels on resting APC, particularly B lymphocytes (20,21). Second, the requirement for initial activation of effector cells before induction of suppressor function imposes a time constraint on when suppression can become manifest.…”
Section: Cd25mentioning
confidence: 99%